Pleomorphic fibroma of the skin with MDM2 immunoreactivity: A potential diagnostic pitfall. (8th November 2017) - Tashakori, Mehrnoosh; Pimentel, Jason; Howitt, Brooke E.; Sanchez, Jessica; Michalowski, Susan; Chitale, Dhananjay; Ormsby, Adrian H.; Williamson, Sean R.
Abstract : Pleomorphic fibroma is a rare benign cutaneous neoplasm characterized by spindle‐shaped cells and multinucleated giant cells scattered throughout collagenous stroma. These morphologic features can lead to diagnostic confusion, including atypical lipomatous tumor as one consideration. In contrast to atypical lipomatous tumor, previous studies have found pleomorphic fibroma to be negative for MDM2 immunohistochemical staining and MDM2 gene amplification. Here, we present a case of pleomorphic fibroma of skin with nuclear MDM2 immunoreactivity in the absence of MDM2 gene amplification, underscoring the superiority of fluorescence in situ hybridization as a diagnostic test in this differential diagnosis. The RB1 locus is also explored for differential diagnosis with pleomorphic/spindle cell lipoma and related entities.